Effectiveness Of Turmeric, Galangal, Guava Leaves, Ketapang Leaves And Cinnamon To Inhibit The Growth Of The Pathogen Bacteria Aeromonas hydrophila: EFEKTIVITAS KUNYIT, KENCUR, DAUN JAMBU BIJI, DAUN KETAPANG DAN KAYU MANIS UNTUK MENGHAMBAT PERTUMBUHAN BAKTERI PATOGEN Aeromonas hydrophila - Ramadhani, Dian Eka; Erlan Hafid, Muhamad; Maula, Athaya; Wafi Nurrafa, Nazla; Sabila Fauziah, Sarah; Masya Grasilla, Dania; Mulanti, Rahmah; Dwi Permana, Shadam; Rafi, Muhammad; Zalfa Fadilah, Siti; Adi Fahrezy, Rafly; Alifian Kautsar, Miem; Dwi Anjani, Resti (IPB University, 2024)
This research aims to obtain the best type and dose of herbal medicine to inhibit the pathogenic bacteria Aeromonas hydrophila growth. This research was conducted at the Laboratory of Health and Environment, Technology and Management of Applied Aquaculture Study Program, College of Vocational Studies, IPB University. This research tested herbal ingredients, including turmeric, galangal, guava, ketapang, and cinnamon, according to their respective doses. Each treatment was tested singly and in combination using the Kirby-Bauer method and co-culture. The parameters measured were the diameter of the inhibition zone and the number of pathogenic bacteria. The results showed that cinnamon leaves could inhibit the growth of the pathogenic bacteria Aeromonas hydrophila to the greatest extent, with an inhibition zone of 11 mm and the smallest number of pathogen colonies growing, namely 0,11 x 109 CFU/mL. The results of the combined test between herbal ingredients, ketapang leaves and papaya leaves produced the highest inhibition zone, namely 9,5 mm. The best results in this research were cinnamon, whether tested single or in combination with ketapang leaves, which was able to reduce the number of pathogenic bacteria Aeromonas hydrophila compared to other treatments.